Secondary School Students’ Perception on Edmodo as Online Learning Platform in English Learning - Prastikawati, Entika Fani; Wiyaka, Wiyaka; Lestari, Maria Yosephin Widarti (Universitas Negeri Semarang, 2022)
Considering the students as digital-natives, the integration of technology in English language learning is needed. It is in line with the 21 -century students required-skills that they have to master information communication and technology (ICT). Hence, Edmodo has been used by English teachers in secondary schools as an online learning platform to support and reach their learning objectives today. This current study aims to look over the secondary students’ perception on the use of Edmodo in English learning. To reach this purpose, a mixed-method approach was applied. Forty students from four different secondary/junior high schools were involved in this study. In collecting the data, a closed-questionnaire consisted of 13 items and a semi-structured interview were carried out. The finding reveals that Edmodo was positively and wellperceived by the secondary students as an acceptable online learning platform for their English learning. Even the problem of an internet connection arises, most of the students admit Edmodo assists them in saving their learning time, reducing learning boredom, and creating better English learning.